A web-based psychoeducational intervention program for depression and anxiety in an adult community in Selangor, Malaysia: protocol of a randomized controlled trial - Kader Maideen, Siti Fatimah; Mohd-Sidik, Sherina; Lekhraj Rampal; Mukhtar, Firdaus; Ibrahim, Normala; Phang, Cheng-Kar; Tan, Kit-Aun; Ahmad, Rozali (JMIR Publications, 2016)
Background: Mental disorders are a major public health problem and are debilitating in many nations throughout the world. Many individuals either do not or are not able to access treatment. The Internet can be a medium to convey to the community accessible evidenced-based interventions to reduce these burdens. OBJECTIVE The objective of this study is to investigate the effectiveness of 4 weeks of a Web-based psychoeducational intervention program for depressive and anxiety symptoms in the community of Selangor, Malaysia. Methods: A two-arm randomized controlled trial of a single-blind study will be conducted to meet the objective of this study. We aim to recruit 84 participants each for the intervention and control groups. The recruitment will be from participants who participated in the first phase of this research. The primary outcomes of this study are depressive and anxiety scores, which will be assessed using the Patient Health Questionnaire 9 and Generalized Anxiety Disorder 7, respectively. The secondary outcome includes mental health literacy of the participants, which will be assessed using the self-developed and adapted Mental Health Literacy Questionnaire. The psychoeducational intervention program consists of four sessions, which will be accessed each week. The depressive and anxiety symptoms will be compared between participants who participated in the psychoeducational program compared with the control group. Depressive and anxiety scores and mental health literacy will be assessed at week 1 and at follow-ups at week 5 and week 12, respectively. Results: The psychoeducational intervention program consists of four sessions, which will be accessed at each week. The depressive and anxiety symptoms will be compared between the intervention and control groups using a series of mixed ANOVAs. Depressive and anxiety scores and mental health literacy will be assessed at week 1 and at two follow-ups at week 5 and week 12, respectively. Conclusions: To our knowledge, this study will be the first randomized controlled trial of a Web-based psychoeducational intervention program for depression and anxiety in an adult community in Malaysia. The results from this study will determine the effectiveness of a psychoeducational intervention program in the management of depression and anxiety among adults in the community. If proven to be effective, the intervention can serve as a new modality to manage and reduce the burden of these disorders in the community.